Discovering the wild side of urban plants through public engagement. Issue 4 (8th April 2021) - Vega, Kevin A.; Schläpfer‐Miller, Juanita; Kueffer, Christoph
Societal Impact Statement: The Anthropocene has seen declining biodiversity inextricably linked to our societies, values, and choices. This requires ecologists to engage with the public in ecosystems such as cities to learn from and help inform their values and experiences regarding their role in urban nature. This article presents a transdisciplinary citizen science project on spontaneous urban vegetation in the context of urban botany, art‐science, and participatory research that engages with the ecology of cities. We address the interdependence of ecological and social networks, suggesting how plant ecology can become more relevant for society in the Anthropocene, while presenting a specific methodology for engaging the public with urban botany. Summary: Cities are socio‐ecological systems that require new ways of thinking and engagement to successfully conserve biodiversity. In this article, we present the citizen science project Where Seeds Fall which was undertaken in the city of Zurich, Switzerland. It was developed in an "ecology with " cities approach seeking to conduct research with the humans living in the ecosystem while learning from and helping inform their values. Our project brings together the perspectives of ecologists, artists, and planners on the three themes of urban wastelands, spontaneous vegetation, and ecological connectivity. It is placed in the context of urban botany, environmental arts and participatory research. Volunteers placed trays of bare soil (without seeds) in their gardens and balconies and monitored what plants arrived and germinated. They then were able to share information about their trays (images, species lists) with one another through a spatially explicit web platform. The project was accompanied by public outreach events and artistic interventions in public space. This article presents the methodology of the project so that it can be replicated elsewhere. Based on the experiences with the project we discuss evolving transdisciplinary perspectives on wild plant biodiversity in cities. Abstract : The Anthropocene has seen declining biodiversity inextricably linked to our societies, values, and choices. This requires ecologists to engage with the public in ecosystems such as cities to learn from and help inform their values and experiences regarding their role in urban nature. This article presents a transdisciplinary citizen science project on spontaneous urban vegetation in the context of urban botany, art‐science, and participatory research that engages with the ecology of cities. We address the interdependence of ecological and social networks, suggesting how plant ecology can become more relevant for society in the Anthropocene, while presenting a specific methodology for engaging the public with urban botany.